2019
DOI: 10.1186/s12875-019-1048-y
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of care for multimorbid patients from the perspective of general practitioners – a qualitative study

Abstract: BackgroundIn Germany, a decreasing number of general practitioners (GPs) face a growing number of patients with multimorbidity. Whilst care for patients with multimorbidity involves various healthcare providers, the coordination of this care is one of the many responsibilities of GPs. The aims of this study are to identify the barriers to the successful coordination of multimorbid patient care and these patients’ complex needs, and to explore the support needed by GPs in the care of multimorbid patients. Inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 33 publications
4
35
0
7
Order By: Relevance
“…A study by Schäfer et al (2017) indicated that one-stop-services provided at GP clinics improved accessibility, continuity and comprehensiveness of care [46]. As GPs are usually burdened by assuming organizational and administrative tasks while providing medical care, assigning the responsibility of arranging and conducting ancillary services to someone else, such as the hiring of PCCs, allowed GPs to focus on the medical care for their patients [47][48][49]. This team-based care approach as studied through a meta-analysis by Levngood et al (2019) established that team-based diabetes management improved overall clinical indicators for diabetes patients, health services utilization, diabetes-related morbidity and mortality [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Schäfer et al (2017) indicated that one-stop-services provided at GP clinics improved accessibility, continuity and comprehensiveness of care [46]. As GPs are usually burdened by assuming organizational and administrative tasks while providing medical care, assigning the responsibility of arranging and conducting ancillary services to someone else, such as the hiring of PCCs, allowed GPs to focus on the medical care for their patients [47][48][49]. This team-based care approach as studied through a meta-analysis by Levngood et al (2019) established that team-based diabetes management improved overall clinical indicators for diabetes patients, health services utilization, diabetes-related morbidity and mortality [50].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Stumm et al (2019) illustrated that the lack of adequate compensation for the coordination of tasks hinders GPs from giving optimal care to their patients [47]. Therefore, funding for manpower to complete back-o ce tasks such as the coordination of ancillary services and consolidation of data elds for the CDR is allocated.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Schäfer et al (2017) indicated that one-stop-services provided at GP clinics improved accessibility, continuity and comprehensiveness of care [25]. As GPs are usually burdened by assuming organisational and administrative tasks while providing medical care, assigning the responsibility of arranging and conducting ancillary services to designated staff allowed GPs to focus on the medical care for their patients [26][27][28]. This team-based care approach as studied through a meta-analysis by Levngood et al (2019) established that team-based diabetes management improved overall clinical indicators for diabetes patients, health services utilisation, diabetes-related morbidity and mortality [29].…”
Section: Discussionmentioning
confidence: 99%
“…A lack of adequate compensation for the coordination of tasks hinders GPs from giving optimal care to their patients [26]. Therefore, funding for manpower to complete back-o ce tasks such as the coordination of ancillary services and consolidation of data elds for the CDR was allocated.…”
Section: Discussionmentioning
confidence: 99%
“…In einer vorangegangenen Interviewstudie desselben Projektes wurden beispielhaft folgende soziale und sozialrechtliche Beratungsanlässe in der Hausarztpraxis genannt: die allgemeine Sozialberatung, die Antragsstellung von Pflegegrad, Rehabilitationsmaßnahmen und Hilfsmitteln, aber auch die Erstellung einer Patient*innenverfügung. Damit geht unter anderem das Ausfüllen einer Vielzahl an Formularen, also administrativer Aufwand einher [4]. Die Ergebnisse aus der Fragebogenerhebung desselben Projektes bestätigen dies [5].…”
Section: Hintergrundunclassified